2019
DOI: 10.1177/1687814019853925
|View full text |Cite
|
Sign up to set email alerts
|

Studying the effects of freeway alignment, traffic flow, and sign information on subjective driving workload and performance

Abstract: Road alignment, traffic flow, and sign information interact and create complex traffic situations. To evaluate the effects of freeway horizontal radius, slope grade, traffic flow, and sign information on subjective driving workload and performance, a simulated driving experiment based on an orthogonal test design was conducted. The National Aeronautics and Space Administration Task Load Index was used to measure self-reported workload. Data regarding speed and lane deviation were collected through the driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the NASA-TLX has been shown to lead to success in driving. Xie [ 23 ] indicated that drivers who experienced a sharp curve scored higher on the NASA-TLX. However, the participants were of a similar age.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NASA-TLX has been shown to lead to success in driving. Xie [ 23 ] indicated that drivers who experienced a sharp curve scored higher on the NASA-TLX. However, the participants were of a similar age.…”
Section: Introductionmentioning
confidence: 99%
“…e supplementary experiment was carried out on the basis of a previous study [35]. e number of subjects increased from 11 to 45 in this research.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 16 simulated driving test scenarios were designed. More details of the scene design parameters can be found in [35].…”
Section: Scenario Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The model involves the road form is similar to the expressway in China, and some studies show that the longitudinal profile of the road has a great influence on traffic safety, especially on the degree of the longitudinal slope of the road [29]. Therefore, this paper draws on the modelling idea of multi-lane expressway accident prediction model in HSM.…”
Section: Establishment Of Black Spot Identification Methods For Expressway Accidentsmentioning
confidence: 99%